A scientometric study of Maqasid al-shariah research: trending issues, hotspot research, and co-citation analysis - Mohammed, Tawffeek A. S. (Frontiers in Research Metrics and Analytics, 2024)
This study examines research on maqāṣid al-shariī'ah in journals indexed in Web of Science (WoS) and Scopus. As maqāṣid al-shariī'ah plays a vital role in guiding Islamic legal theory and contemporary applications of Islamic law in various sectors of life, familiarity with the scholarly landscape of the field is essential for assessing its growing influence in both academic and practical contexts. Hence, this study aims to explore the trajectory of research in maqāṣid studies, identify its key focus areas, and conduct a document co-citation analysis to uncover patterns in scholarly collaboration and influence. In addition, the study examines contributing countries, organizations, and leading journals in this field. Four Hundred documents published between 2000 and 2022 were retrieved and analyzed using the metrics functionalities of both databases. In addition, advanced analytical tools including Publish or Perish, VOSviewer, and ScientoPy v1.3.5 were utilized to conduct a multifaceted examination that encompasses document co-citation, sources co-citation, and authors' keyword analyses, among others. Data were carefully filtered to include research related to maqāṣid al-shariī'ah as an area of applied Islamic thought and its applications in different disciplines. The findings of the study revealed that research outputs in maqāṣid al-shariī'ah studies span various disciplines including religion, business and economics, science and technology, and medicine among others. The development of publications between 2000 and 2022 for the two databases indicates distinct upward trends in cumulative publications and annual growth. A vibrant and diverse global research landscape exists for maqāṣid al-shariī'ah, with Malaysia and Indonesia leading in terms of productivity and impact. This article presents original findings which may be of significance to researchers in Islamic studies, applied Islamic thought, and related interdisciplinary and multidisciplinary fields. This scientometric study is limited to English journal articles that were published between 2000 and 2022 on maqasid research in Scopus and Web of Science (WoS). Given the dynamic nature of these two databases, where results can fluctuate rapidly due to the continuous addition of new papers or the retraction of existing articles, this study is limited to the datasets that were created at the time of investigation. These limitations might influence the generalizability of the findings.